2023
DOI: 10.3390/nu15040959
|View full text |Cite
|
Sign up to set email alerts
|

“Mars Bar and a Tin of Red Bull Kept Me and My Patients Alive”: Exploring Barriers to Healthy Eating through Facebook Comments of Shiftworkers

Abstract: The negative impact of an unhealthy diet on the shiftworker population has been well-documented. However, little evidence exists on the underlying reasons for unhealthy eating behaviours and the existing barriers to healthy eating withinshiftwork environments. This qualitative study investigated the dietary behaviours reported by shiftworkers through Facebook comments. Comments were collected if they were on public shiftworker-relevant posts pertaining to dietary news or dietary information on Facebook and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…Other workers reported that the continuity of care for patients was more complicated with fewer quick returns. These align with another study on shift work showing that healtcare night shift workers tend to skip meals at work for the benefit of the patients’s care [ 12 ] and may thus reflect the healthcare workers’ representations of their work. It may also be a reflection that getting good sleep is not a priority for some of these individuals and is sacrificed to perform better at work.…”
supporting
confidence: 83%
“…Other workers reported that the continuity of care for patients was more complicated with fewer quick returns. These align with another study on shift work showing that healtcare night shift workers tend to skip meals at work for the benefit of the patients’s care [ 12 ] and may thus reflect the healthcare workers’ representations of their work. It may also be a reflection that getting good sleep is not a priority for some of these individuals and is sacrificed to perform better at work.…”
supporting
confidence: 83%